Effect of age and frailty on the efficacy and tolerability of once‐weekly selinexor, bortezomib, and dexamethasone in previously treated multiple myeloma. Issue 6 (3rd May 2021) - Auner, Holger W.; Gavriatopoulou, Maria; Delimpasi, Sosana; Simonova, Maryana; Spicka, Ivan; Pour, Ludek; Dimopoulos, Meletios A.; Kriachok, Iryna; Pylypenko, Halyna; Leleu, Xavier; Doronin, Vadim; Usenko, Ganna; et al.
Abstract: Elderly and frail patients with multiple myeloma (MM) are more vulnerable to the toxicity of combination therapies, often resulting in treatment modifications and suboptimal outcomes. The phase 3 BOSTON study showed that once‐weekly selinexor and bortezomib with low‐dose dexamethasone (XVd) improved PFS and ORR compared with standard twice‐weekly bortezomib and moderate‐dose dexamethasone (Vd) in patients with previously treated MM. This is a retrospective subgroup analysis of the multicenter, prospective, randomized BOSTON trial. Post hoc analyses were performed to compare XVd versus Vd safety and efficacy according to age and frailty status (<65 and ≥65 years, nonfrail and frail). Patients ≥65 years with XVd had higher ORR (OR 1.77, p  = .024), ≥VGPR (OR, 1.68, p  = .027), PFS (HR 0.55, p  = .002), and improved OS (HR 0.63, p  = .030), compared with Vd. In frail patients, XVd was associated with a trend towards better PFS (HR 0.69, p  = .08) and OS (HR 0.62, p  = .062). Significant improvements were also observed in patients <65 (ORR and TTNT) and nonfrail patients (PFS, ORR, ≥VGPR, and TTNT). Patients treated with XVd had a lower incidence of grade ≥ 2 peripheral neuropathy in ≥65 year‐old (22% vs. 37%; p  = .0060) and frail patients (15% vs. 44%; p  = .0002). Grade ≥3 TEAEs were not observed more often in older compared to younger patients, nor in frail compared to nonfrail patients. XVd is safe and effective in patients <65 and ≥65 and in nonfrail and frail patients with previously treated MM.